International Symposium on Inorganic Fluorides: Chemistry and Technology (ISIF-2014) book of abstracts, June 2-6, 2014, Tomsk - Mitkin; Ostvald Chemical Engineer Associate Professor of Tomsk Polytechnic University, Candidate of chemical sciences (TPU Publishing House, 2014)
The book of abstracts covers the wide range of researcli and investigations in the field of fluorine chemistry being carried out by the leading researchers from Russia and worldwide.The theses in this book of abstracts cover all main areas of fluorine chemistry: inorganic, organic, physical, analytical, material science, etc.